Post hysterectomy fallopian tubal prolapse: a diagnostic dilemma - Ramamoorthy, Sowbarnika; Bala, Prithviram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Fallopian tubal prolapse into the vaginal vault is a relatively rare postoperative complication after hysterectomy with adnexal preservation. The exact incidence is not known due to failure to diagnose and under-reporting. We hereby report a case who presented with unexplained vaginal bleeding post-hysterectomy, which was subsequently diagnosed and managed successfully.